Fragmentasi penggunaan ruang jalan di Kampung Pecinan Semarang, Indonesia - Christin Purnamasari Nusaputra; Yohanes Basuki Dwisusanto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
As a trade center, Semarang Chinatown contributes to developing the economic activities of the city. The expansion of the economic network creates various opportunities through informal activities. This is reflected in the inclusiveness of the local community, using roads as venues of economic activities, especially on Gang Baru Street in Semarang Chinatown. The street connects the neighborhood, accommodates informal activities, and serves as a traditional market. Furthermore, it has been privatized by trading activities from the shophouses and street vendors. The claim trend has commodified the formal use of the street as access infrastructure. Consequently, the differences in formal and informal activities cause the use of road space to be fragmented. Therefore, this study examines the fragmented use of Gang Baru street caused by the segmented informal activity interests. The qualitative method is used for a thorough bottom-up observation of the street’s activities. Various activities are classified based on the street user segmentation by organizational practices and spontaneous community behavior. This categorization is also based on the users’ participatory or antagonistic response to the street’s formal use. The result shows activity diversity portrays a dialectic interest representing the fragmented use of Gang Baru Street.